Становление угольной промышленности конца ХІХ – начала ХХ века (на примере города Снежное Донецкой области) - Бривко, Н.В. (Історичний архів. Наукові студії, 2014)
Работа посвящена проблеме развития угольной промышленности Донбасса конца
ХІХ – начала ХХ века на примере города Снежное. Данный материал
охарактеризовывает положение и развитие угольной промышленности, дается
анализ становления капиталистических отношений в городе Снежное. Раскрывается
условия труда на угольных предприятий и быта рабочих города Снежного. Делается
вывод об определяющей роли угольной промышленности в историческом развитии
Донбасса на примере города Снежное. Праця присвячена проблемі розвитку вугільної промисловості Донбасу кінця ХІХ –
початку ХХ століття на прикладі міста Сніжне. Даний матеріал характеризує
положення й розвиток вугільної промисловості, подає аналіз становлення
капіталістичних відносин в місті Сніжне. Розкриваються умови праці на вугільних
підприємствах на побут робітників міста Сніжне. Робиться висновок про визначальну
роль вугільної промисловості в історичному розвитку Донбасу на прикладі міста Сніжне. The study provides an analysis of the development of the coal industry, clarified and
summarized the objective and subjective reasons, have impeded development in the pre-reform
period. There is, as a result of changes in geopolitical and geostrategic position, the Russian
Empire changed Government priorities in the development of the coal industry and the entire
heavy industry, which was transferring her to the South of the Russian Empire, and the Basin
with its natural wealth and advantageous geographical position has gained strategic importance
for the country, including the city of Snezhnoye.
Traced and identified main stages and areas the development of coal deposits in the snow.
The peculiarities of development of coal sector of Donbass in conditions of the industrial
revolution, it traces the transformation of the region into fuel and energy base. Studied the
formation of major coal mining companies in the snow. Analyses the causes of large enterprises
with small-scale coal mining fishing and its impact on the environment of the coal market.
Examines the process of monopolization of the coal of Donbass in enterprises of the city
Snezhnoye.
On the basis of a comparison and study of the memories of eyewitnesses are working and
living conditions of the miners of Snezhnoye, as one of the greatest power among the
proletariat.
On the basis of material of research, concludes on the decisive role of the coal industry in
the historical development of the region and the city of Snezhnoye and his influence in shaping
the socio-economic, ethno-national, cultural and mental environment.